Feasibility and Current Applications of the Symani Surgical System: A Systematic Review - Yu Jin Jeong, MD; Amanda E. Yung, MD; Daniel Steffens, PhD; Sophie Hogan, PhD; Jonathan R. Clark, AM, MBiostats; Sydney Ch’ng, MBBS, PhD, FRACS, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. The application of robotics in microsurgery remains to be widely established. Currently, the Symani Surgical System (Medical Microinstruments, Pisa, Italy) remains the only commercially available robotic platform dedicated to microsurgery. This systematic review evaluated the current evidence surrounding the Symani, including current applications, operating time and learning curve, ergonomics, limitations, and clinical outcomes. Methods:. A comprehensive search was conducted via Ovid in MEDLINE, Embase, and the Cochrane Library from inception to September 2024. The review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines and registered in PROSPERO (CRD42024616049). Results:. The initial search identified 98 records, of which 7 preclinical and 17 clinical studies were included. All included studies were conducted within European centers, with an increasing number of publications over the last 3 years (2022, n = 3; 2023, n = 7; 2024, n = 14). Most clinical studies were case reports (n = 6) or series (n = 9). The clinical application of the Symani for lymphatic surgery (n = 7), nerve repair (n = 4), and vascular anastomosis (n = 11) have been described. Early data suggest longer anastomotic times and steep learning curves with the Symani. High rates of intraoperative anastomosis patency (>90%) have been demonstrated, but remain to be evaluated in head-to-head comparisons with conventional methods. Conclusions:. Early clinical outcomes demonstrate the feasibility of Symani-assisted microsurgery. Comparative studies are required to assess the benefit of robotic-assisted microsurgery over conventional methods, particularly for vessels less than 0.8 mm in diameter, that is, supermicrosurgery.